Chanamé Orbe, Raúl. The utopia of democracy. History of suffrage in Peru (1808-1933). From the constitutions of Bayonne and Cádiz to the origin of the National Jury of Elections. Editorial National Jury of Elections, 2020, 1st. Ed., Pp. 400. - Peruana de Derecho Internacional, Sociedad (2020)
Editorial National Jury of Elections, 2020, 1st. Ed., Pp. 400.